Предмет: Математика,
автор: romanoblat7
6x−5y+8x−7y=
9m+12−8−4m=
−7a+5−3a+2=
5a−12b−7a+5b=
17x−(4x−5)=
(7a−4)−(4a+2)=
−(5x−y)+(4x+5y)=
(−5a+b)−(−2b+4a)+(7a−3b)=
Пожалуста помогите
romanoblat7:
Це Спрощеня виразів
Ответы
Автор ответа:
0
6х - 5у + 8х - 7у = 14х - 12у
9m + 12 - 8 - 4m = 5m + 4
- 7a + 5 - 3a + 2 = 7 - 10a
5a - 12b - 7a + 5b = - 2a - 7b
9m + 12 - 8 - 4m = 5m + 4
- 7a + 5 - 3a + 2 = 7 - 10a
5a - 12b - 7a + 5b = - 2a - 7b
Похожие вопросы
Предмет: Английский язык,
автор: vika018
Предмет: Русский язык,
автор: Artem332
Предмет: Русский язык,
автор: Nastya29032002
Предмет: Математика,
автор: dim4169
Предмет: Математика,
автор: даня2604